Optimal type and dose of hypoxic training for improving maximal aerobic capacity in athletes: a systematic review and Bayesian model-based network meta-analysis - Zhao, L.; Feng, X.; Chen, Y.; Wang, Z.; Lu, H.; Wang, C. (Frontiers in Physiology, 2023)
Objective: This study aimed to compare and rank the effect of hypoxic practices on maximum oxygen consumption (VO2max) in athletes and determine the hypoxic dose-response correlation using network meta-analysis.